2019
DOI: 10.1002/mrd.23156
|View full text |Cite
|
Sign up to set email alerts
|

Altered morphokinetics in equine embryos from oocytes exposed to DEHP during IVM

Abstract: Di‐(2‐ethylhexyl) phthalate (DEHP) is a commonly used plasticizer with endocrine‐disrupting properties. In this study, we used an equine model to investigate DEHP concentrations in ovarian follicular fluid (FF), and to determine the effects of exposure of oocytes to potentially toxic concentrations of DEHP during in vitro maturation (IVM) on embryo development and quality. Embryo development was evaluated using time‐lapse monitoring (TLM), a photomicroscopic tool that reveals abnormalities in cleavage kinetics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 102 publications
(160 reference statements)
1
7
0
Order By: Relevance
“…To thebest of our knowledge, the present study is the first to closely examine equine preimplantation development to the blastocyst stage via TLM with oocytes obtained by OPU from mares of various breeds (both draft and non-draft) that are commonly used as oocyte donors and surrogates for embryo transfer. Marzano et al (2019) also determined that the duration of the second cell cycle, or the time between the first and second mitosis, as reported here, was, 17 h in controls, whereas the time between second and third mitotic division was, 6 h, both of which had large standard deviations. In the present study we demonstrated that the time intervals between the first and second, as well as the second and third, divisions in those equine embryos that formed blastocysts was, 7-10 h and, 1-3 h respectively, with significantly less variation and closer to that observed in human embryos (Wong et al 2010;Chen et al 2013).…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…To thebest of our knowledge, the present study is the first to closely examine equine preimplantation development to the blastocyst stage via TLM with oocytes obtained by OPU from mares of various breeds (both draft and non-draft) that are commonly used as oocyte donors and surrogates for embryo transfer. Marzano et al (2019) also determined that the duration of the second cell cycle, or the time between the first and second mitosis, as reported here, was, 17 h in controls, whereas the time between second and third mitotic division was, 6 h, both of which had large standard deviations. In the present study we demonstrated that the time intervals between the first and second, as well as the second and third, divisions in those equine embryos that formed blastocysts was, 7-10 h and, 1-3 h respectively, with significantly less variation and closer to that observed in human embryos (Wong et al 2010;Chen et al 2013).…”
Section: Discussionsupporting
confidence: 67%
“…Time-lapse image analysis of human oocyte maturation, fertilisation and preimplantation embryogenesis was initially reported several years ago (Payne et al 1997;Hardarson et al 2002) but only recently used to evaluate embryos from other mammalian species (Pribenszky et al 2010;Sugimura et al 2010Sugimura et al , 2012Weinerman et al 2016). Using abattoirderived equine ovaries from draft mares, Marzano et al (2019) showed differences in the time of second polar body extrusion and duration of the second cell cycle between control and di-(2ethylhexyl)phthalate (DEHP)-treated oocytes. To thebest of our knowledge, the present study is the first to closely examine equine preimplantation development to the blastocyst stage via TLM with oocytes obtained by OPU from mares of various breeds (both draft and non-draft) that are commonly used as oocyte donors and surrogates for embryo transfer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A level of ~20 nM MEHP was detected in the follicular fluid aspirated from the DEHP-treated cows ( Kalo et al., 2015 ). Similarly, a level of ~10 nM DEHP was recorded in equine follicular fluid ( Marzano et al., 2019 ). Non-DEHP-originated metabolites such as monoethyl phthalate and monobutyl phthalate were also detected in the follicular fluid, presumably of environmental origin ( Kalo et al., 2015 ).…”
Section: Phthalatesmentioning
confidence: 90%